Determinants of Inflation in Western Europe - Lilis Ayu Widyaningsih; Eni Setyowati (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This paper attempts to examine the impact of trade openness, economic growth (GDP), and gas price on inflation in Western European countries. Utilizing panel data from seven countries over the period 2020–2024, the research employs the Fixed Effect Model (FEM) as the most appropriate estimation approach, as determined by the Chow and Hausman tests. The results reveal that trade openness and gas price exert a significant positive influence on inflation, whereas economic growth shows no significant effect. These findings suggest that inflation in Western Europe is predominantly driven by external factors, particularly fluctuations in energy prices and global trade dynamics.